A Comparative Analysis of Minority Political Participation from an Islamic Perspective in Indonesia and Singapore - Syarif, Mujar Ibnu; Kharlie, Ahmad Tholabi; Purkon, Arip (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This study aims to examine the Islamic political concept of minority political participation and compare its implementation in the contexts of Indonesia and Singapore. The research is a qualitative study utilizing a comparative method, combined with descriptive and analytical approaches. The data sources are twofold: primary sources, such as the Constitutions of the Republic of Indonesia and Singapore, and secondary sources, including several academic works relevant to the research topic, sourced from both print and online media. Data analysis was carried out in four stages: data collection, reduction, presentation, and conclusion drawing. The findings of this study indicate that political participation refers to the actions of citizens to influence government policies, enabling the government to be guided towards issuing egalitarian policies. Minorities in Indonesia include Protestants, Catholics, Buddhists, Hindus, and Confucians, while minorities in Singapore comprise Muslims, Christians, Hindus, Confucians, Taoists, and atheists. Indonesia is a moderate country that blends Islamism and secularism, whereas Singapore is a secular state. The conclusion of this study reveals that most Islamic scholars argue that non-Muslim minorities cannot fully participate in politics unless in emergency situations. On the other hand, liberal Muslim intellectuals believe that non-Muslims can fully participate in politics, even outside of emergency contexts. The majority of Muslim intellectuals in both Indonesia and Singapore allow full political participation for minorities, including becoming president, as there are no restrictions in either country preventing minorities from holding the presidency. The comparative analysis shows that minorities in both Indonesia and Singapore have equal standing with the majority. However, in Indonesia, no minority has yet succeeded in becoming President, whereas in Singapore, Halimah Yacob, a Muslim minority, became the country’s first female president.